2013
DOI: 10.1016/j.vaccine.2013.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of 10- and 13-valent pneumococcal conjugate vaccines: Protection at what price in the Thai context?

Abstract: At current prices, PCV10 and PCV13 are not cost-effective in Thailand. Inclusion of indirect vaccine effects substantially reduced the ICERs for both vaccines, but did not result in cost effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 32 publications
1
55
1
Order By: Relevance
“…However, the Thailand study showed that at current prices, PCV10 and PCV13 are not cost-effective even with the inclusion of vaccine herd effects. 19 However, there have been similarities of 3 studies in that all have utilized state-transition Markov model, and applied country-specific serotype data to adjust for vaccine effectiveness on vaccinated and unvaccinated populations. Contrary to our study results, a prior study in Malaysia concluded that a PCV10 program was cost-effective compared with PCV13.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Thailand study showed that at current prices, PCV10 and PCV13 are not cost-effective even with the inclusion of vaccine herd effects. 19 However, there have been similarities of 3 studies in that all have utilized state-transition Markov model, and applied country-specific serotype data to adjust for vaccine effectiveness on vaccinated and unvaccinated populations. Contrary to our study results, a prior study in Malaysia concluded that a PCV10 program was cost-effective compared with PCV13.…”
Section: Discussionmentioning
confidence: 99%
“…A Markov model with one-year cycle length adapted from a prior study [14] was used to estimate the lifetime costs and outcomes for PCV10 and PCV13 compared to 'no vaccination', consisting of three major health states: good health, S. pneumoniae infection and death (Fig 1). Whilst the model structure for this study was adapted from Thai setting, this model has been validated in consultation meetings by Philippine experts including infectious disease specialists, epidemiologists, health economists, and policy decision makers.…”
Section: Markov Modelmentioning
confidence: 99%
“…For PCV13, demonstration of VE is based on non-inferior immunogenicity compared with PCV7 rather than efficacy trials measuring clinical endpoints [28,29]. However, evidence supporting the effectiveness of PCV13 for covered serotypes has been documented in various [14] (Continued)…”
Section: Model Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining four LLMIC studies used arbitrary thresholds or compared against interventions that were already implemented. Two of the three UMIC studies that used another threshold were set in Thailand and used Thailand's national threshold of GNI per QALY gained (Kulpeng et al , , Rattanavipapong et al , ).…”
Section: Resultsmentioning
confidence: 99%